Digitalisation as Enabler Towards a Sustainable Circular Economy in Germany - Adriana Neligan (Intereconomics, 2018)
The increasing use of digital networking in complex industrial processes opens up new potential for more sustainability. This paper delivers the fi rst empirical fi ndings on the relevance of digitalisation for improving material effi ciency in German industry based on a unique dataset including nearly 600 manufacturing fi rms. The survey results indicate that the opportunities of digital networking for increasing material effi ciency are only being used to a limited extent thus far, primarily for traditional effi ciency-raising measures optimising manufacturing processes.
Keywords: 330